Synthesis and Characterization of PbS Quantum Dots Embedded in Oxide Glass - A. M. Alcalde (Brazilian Journal of Physics, 2006)
The fusion method was used to produce PbS quantum dots (QDs) embedded in S-doped glass matrix (SiO2-Na2CO3-Al2O3-PbO2-B2O3:S). Measurements of optical absorption (OA), photoluminescence (PL) and atomicforce microscopy (AFM) have been carried out in order to characterize the produced QDs. A strong red-shiftobserved in the optical features with an increase of the annealing time indicates an increase in QD-size. The QDsizes predicted by k.p theoretical results were confirmed by AFM observation.